Faktor Penyebab dan Solusi Terhadap Penurunan Motivasi Belajar Siswa Sekolah Dasar di Era Digital - Kamaratih Noor, Maulida; Syafi'e, Muhammad; Merliana Sari, Ruli; Noviantul, Witha; Suriansyah, Ahmad; Refia Rafianti, Wahdah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital era has brought significant changes to the learning patterns of elementary school students and has significantly influenced their level of learning motivation. Various findings show that easy access to digital technology often causes distraction, reduces focus, and shifts interest in learning to entertainment activities. Although much research has addressed the impact of technology, there is still a gap in understanding how these factors relate to each other and influence overall learning motivation. This research uses a literature study approach to identify a general picture of the causes of decreased student learning motivation in the digital era as well as patterns of problems that arise in the learning process. Analysis shows that changes in learning environments and increased digital exposure contribute to weakening students' learning drive. This research is important to provide understanding for educators and parents in developing strategies that are more flexible to student needs, and emphasizes the need for further studies to formulate more effective solutions in the digital era.